Matriculture Among Circumpolar Peoples: Introduction - Angnakak, Sharon (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2026)
This issue of Matrix centres upon voices that speak about Northern women who are central to negotiating cultural change and who remain for their communities a source of cultural continuity. In drawing out these voices from circumpolar matricultures, this issue’s submissions examine women’s land-based economies on the tundra and taiga and women’s artistic practices, as well as presenting a collection of interviews from circumpolar women recently recorded by the Editorial Collective of Matrix; its collection contributes to a broader body of women’s knowledge that complements the archival record.Throughout the issue, themes of cultural change and continuity are explored, showcasing how circumpolar communities and cultures are sustained through women’s labour, their participation in local economies, and through their community leadership essential in navigating and negotiating the cultural change brought on by intercultural contact, changing geopolitical tensions, and the evolving technological realities that move and shape globalism. Whether through beadwork, narrative, or land-based practices, Indigenous and circumpolar women continue to sustain and transform their cultural knowledge across generations, ensuring its continuity not through strict adherence to a preserved archetype, but through ongoing practices – women’s labour – that constantly renew culture into new expressions while ensuring their community’s survival.